Analisis Tata Letak Fasilitas Sero Elite Farm dengan Metode Activity Relationship Chart (ARC) dan Total Closeness Rating (TCR) - Aulia, Muhammad Faris; Baldan, Raditya Seivel; Ardiningrum, Aisha Kurnia; Aisyah, Alya; Himawan, Dennis (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze and redesign the facility layout of Sero Elite Farm using the Activity Relationship Chart (ARC) and Total Closeness Rating (TCR) methods. The analysis focuses on improving operational efficiency through adjustments to the spatial proximity of key facility functions. The results indicate that placing the feed storage area closer to the fish pond streamlines feeding activities and enhances employee productivity. The warehouse was repositioned near the parking area to facilitate material movement, while the sales area was relocated closer to the main road access from the north to improve customer convenience in purchasing daily fish products. The redesigned layout provides a more effective workflow, reduces unnecessary movement, and supports the farm’s overall operational efficiency.